2016
DOI: 10.1002/cpp.1961
|View full text |Cite
|
Sign up to set email alerts
|

Using the Repertory Grid Technique to Examine Trainee Clinical Psychologists' Construal of Their Personal and Professional Development

Abstract: Clinical psychology trainees experience training as demanding and stressful, which negatively impacts on their personal and professional self-image and self-esteem. However, they are optimistic that they will become more like their ideal self in the future. Stress in clinical training (and beyond) is normative, and thus, personal development and self-care should be recognized as clinical psychologist's core competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The gathered data not only on factors required for success, but the relative importance of each factor to the concept of successful practice (White, 1996). It is a methodology commonly employed in Job Analysis i.e., describing jobs and the attributes required to perform them, and provides the workers' perspective (Hill et al, 2016;Hamad et al, 2017;Burke, 2022). The Repertory Grids were analyzed, visualized as 'mental maps' of job satisfaction and dissatisfaction aspects, and they were related to NPS expressing satisfaction with working conditions, training and intention to stay.…”
Section: Designmentioning
confidence: 99%
“…The gathered data not only on factors required for success, but the relative importance of each factor to the concept of successful practice (White, 1996). It is a methodology commonly employed in Job Analysis i.e., describing jobs and the attributes required to perform them, and provides the workers' perspective (Hill et al, 2016;Hamad et al, 2017;Burke, 2022). The Repertory Grids were analyzed, visualized as 'mental maps' of job satisfaction and dissatisfaction aspects, and they were related to NPS expressing satisfaction with working conditions, training and intention to stay.…”
Section: Designmentioning
confidence: 99%
“…Research has shown that work-life imbalance (e.g., high case load; workaholism) is related to the experience of work stress and compassion fatigue (Killian 2008). Poor work-life balance has also been linked to exhaustion among mental health practitioners (Scanlan et al 2013) and feelings of anxiety, stress, and being unsettled (Hill et al 2016). In contrast, maintaining balance in life is related to lower levels of emotional exhaustion (Rupert and Kent 2007), greater career satisfaction (Rupert et al 2012), and lower risk of burnout (Levin et al 2017).…”
Section: Balancementioning
confidence: 99%
“…The RGT is “a form of structured interviewing, with ratings or without, which arrives at a precise description uncontaminated by the interviewer’s own viewpoint” (Jankowicz, 2004, p. 14) and is a methodological application of the PCT (Hair, Rose, & Clark, 2009). The RGT has been applied to social (Hair et al, 2009; Hill, Wittkowski, Hodgkinson, Bell, & Hare, 2016), business (Klapper, 2014), consumer (Marsden & Littler, 2000), and clinical fields of research (Beail, 1985; Cridland, Caputi, Jones, & Magee, 2014; McNair, Woodrow, & Hare, 2016). The RGT has been used with various research aims but is more commonly used to develop theory that is grounded (Patton, 2002) or when the literature is limited (Easterby-Smith, Thorpe, & Lowe, 2002; Eisenhardt, 1989).…”
Section: Rgtmentioning
confidence: 99%